2017
DOI: 10.18632/oncotarget.14932
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy degrades the quality of life of patients with stage II nasopharyngeal carcinoma as compared to radiotherapy

Abstract: The purpose of this study was to compare the quality of life (QoL) of stage II nasopharyngeal carcinoma (NPC) patients treated with radiotherapy (RT) versus concurrent chemoradiotherapy (CCRT). In a cross-sectional study, these patients were treated with RT (n = 55) or CCRT (n = 51) between June 2008 and June 2013. For all subjects, disease-free survival was more than 3 years. QoL was assessed using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…In the study reported by Cengiz et al for NPC patients treated by 2D‐RT, they observed that neoadjuvant or adjuvant chemotherapy did not have any effect on QOL, whereas concurrent chemotherapy adversely affected some symptom scales (insomnia, social eating, feeling ill, weight gain, and the need of nutritional supplement) . In the other study by Pan et al, they also observed that the combination of chemotherapy in patients whatever treated by 2D‐RT or IMRT had worse effect in QOL scales, including global QOL, functional scales, symptom scales of fatigue and insomnia, financial problems, and weight gain …”
Section: Discussionmentioning
confidence: 93%
“…In the study reported by Cengiz et al for NPC patients treated by 2D‐RT, they observed that neoadjuvant or adjuvant chemotherapy did not have any effect on QOL, whereas concurrent chemotherapy adversely affected some symptom scales (insomnia, social eating, feeling ill, weight gain, and the need of nutritional supplement) . In the other study by Pan et al, they also observed that the combination of chemotherapy in patients whatever treated by 2D‐RT or IMRT had worse effect in QOL scales, including global QOL, functional scales, symptom scales of fatigue and insomnia, financial problems, and weight gain …”
Section: Discussionmentioning
confidence: 93%
“…First, patients who received CCRT or CCRT+AC showed more acute and late toxicity reactions without a substantial survival benefit [ 8 10 ]. Second, compared to RT alone, CCRT impaired the quality of life of stage II NPC patients [ 39 ]. Third, because the cost of chemotherapy for NPC is high, overuse of chemotherapy imposes a considerable economic burden on society, especially in developing countries such as China [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, compared to RT alone, CCRT impaired the quality of life of stage II NPC patients [ 39 ]. Third, because the cost of chemotherapy for NPC is high, overuse of chemotherapy imposes a considerable economic burden on society, especially in developing countries such as China [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 A wealth of studies have shown that IMRT could improve OS mainly by reducing local and regional recurrence rates compared to conventional RT, in addition to resulting in a better quality of life (QOL) and having a more acceptable toxicity for NPC patients. [10][11][12][13] Given these findings, some researchers have attempted to explore the effect of IMRT alone for stage II patients with an aim to achieve survival outcomes comparable to those obtained with CCRT but with less associated toxicity.…”
Section: Treatment Patterns For Stage II Npc Imrt Alonementioning
confidence: 99%